Privatisation of municipal solid waste management in Malaysia / Zainudin Awang, Safri Ya and Wan Zumusni Wan Mustapha - Awang, Zainudin; Ya, Safri; Wan Mustapha, Wan Zumusni (2005)
Privatisation is a single, but significant element of policies aimed at reducing the role of government and increasing the role of private sectors in a modem economy. In Malaysia, the privatisation policy was promulgated by former Prime Minister, Tun Dr Mahathir in 1983 when the country faced the worse economic crisis in the early 1980s. since then, almost 500 public enterprises had been privatized, including privatisation of municipal solid waste management. Privatisation of municipal solid waste management in Malaysia started in 1994. The principle of privatisation of municipal solid waste management is aimed to improve the quality of service and promote efficiency in municipal solid waste management through taking over the municipal's responsibility and function by the consortium awarded the concession agreement i.e Alam Flora, Nothem Waste management, Southern Waste management and Eastern Waste management. Today, privatisation of municipal solid waste management is still in the transition or interim period. The interim agreement between municipalities and consortia is on monthly basis, and municipalities pay consortia every month for the service provided. This study examines the process and rational of privatisation of municipal solid waste management in Malaysia. II looks at the implementation of privatisation during the interim period. The Issues and problems emerged during the Interim period are highlighted. The study is also analyzed the impact of privatization during the Interim period i.e. impact on municipality sector, impact on public workers, impact on solid waste management system and soon. The contextual issues i.e management and institutional context and financial and cost recovery context are also studied. In doing so, similarly efficiency and effectiveness of solid waste management investigated too. Data was gathered from the case study of consortium in MPPJ, namely Alam Flora an Majlis Perbandaran Petaling Jaya. Another case study is done on Majlis Perbandaran Pulau Pinang, Majlis Perbandaran Kata Bharu for effectiveness and efficiency of solid waste collection. The time and motion studies are also done as part of the data collection methods in the above mentioned city councils. Finally, this study posit that full privatisation of municipal solid waste management as a solution towards a more efficient solid waste management system in Malaysia.